Old artifiсial parks as a key spot of corticolous lichen diversity in Southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Old artificial parks are an important component of the cultural heritage in Southern Ukraine which represents a significant variety of specific habitats for lichen diversity. The aim of our research was to analyze the total lichen diversity in parks as well as the representation of rare and protected species. Most of the data were collected by the authors during expeditions in Southern Ukraine during 2017–2020 in Kherson and Mykolaiv regions. Overall, we identified 108 lichen species and 21 lichenicolous fungi within 17 old parks. The highest lichen diversity was recorded in parks “Labirynt” (66 species) and “Nedogirskyi Forest” (61 species). We found 18 lichen species (16.6 %) included in the Red List of Kherson and Mykolaiv regions and 25 (23.8%) rare forest-dwelling species. We concluded that old artificial parks are very important habitats for lichen diversity in the steppe zone of Ukraine as well as the unique localities for such species as Graphis scripta, Hyperphyscia adglutinata, Sclerophora pallida in Southern Ukraine. The total diversity of lichens did nоt have a significant correlation with the total number of tree species due to the dominance of several tree species (Fraxinus excelsior, Quercus robur), while most other phorophytes are young and represented singly. All old parks should become local reserves to preserve the overall biological diversity in their territories, protect against illegal logging, and regulate potential recreational activities.
Keywords: biodiversity, Graphis, Hyperphyscia, Sclerophora, Mykolaiv, Kherson, rare species.